Heparin-Binding Protein as a Prognostic Biomarker of Sepsis and Disease Severity at the Emergency Department. Issue 6 (December 2019) - Kahn, Fredrik; Tverring, Jonas; Mellhammar, Lisa; Wetterberg, Nils; Bläckberg, Anna; Studahl, Erika; Hadorn, Niklas; Kahn, Robin; Nueesch, Susanne; Jent, Philipp; Ricklin, Meret E.; Boyd, John; et al.
ABSTRACT: Objective: Rapid and early detection of patients at risk to develop sepsis remains demanding. Heparin-binding protein (HBP) has previously demonstrated good prognostic properties in detecting organ dysfunction among patients with suspected infections. This study aimed to evaluate the plasma levels of HBP as a prognostic biomarker for infection-induced organ dysfunction among patients seeking medical attention at the emergency department. Design: Prospective, international multicenter, convenience sample study. Setting: Four general emergency departments at academic centers in Sweden, Switzerland, and Canada. Patients: All emergency encounters among adults where one of the following criteria were fulfilled: respiratory rate >25 breaths per minute; heart rate >120 beats per minute; altered mental status; systolic blood pressure <100 mm Hg; oxygen saturation <90% without oxygen; oxygen saturation <93% with oxygen; reported oxygen saturation <90%. Intervention: None. Measurements and Main Results: A total of 524 emergency department patients were prospectively enrolled, of these 236 (45%) were eventually adjudicated to have a noninfectious disease. Three hundred forty-seven patients (66%) had or developed organ dysfunction within 72 h, 54 patients (10%) were admitted to an intensive care unit, and 23 patients (4%) died within 72 h. For the primary outcome, detection of infected-related organ dysfunction within 72 h, the area under the receiver operating curve (AUC) for HBP was 0.73 (95% CI 0.68–0.78) among all patients and 0.82 (95% CI 0.76–0.87) among patients confidently adjudicated to either infection or no infection. Against the secondary outcome, infection leading to admittance to the ICU, death or a persistent high SOFA-score due to an infection (SOFA-score ≥5 at 12–24 h) HBP had an AUC of 0.87 (95% CI 0.79–0.95) among all patients and 0.88 (95% CI 0.77–0.99) among patients confidently adjudicated to either infection or noninfection. Conclusions: Among patients at the emergency department, HBP demonstrated good prognostic and discriminatory properties in detecting the most severely ill patients with infection. Abstract : Supplemental Digital Content is available in the text